2013
DOI: 10.1002/pssb.201349215
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and magnetic properties of Co2−xFexCrAl alloys: Ab initio calculations

Abstract: We performed density functional theory (DFT) calculations within the full-potential linearized augmented plane wave (FLAPW) method to study the electronic and magnetic properties of Co 2Àx Fe x CrAl (x ¼ 0, 0.25, 0.5, 0.75, and 1) alloys. The calculations indicate that Co 2Àx Fe x CrAl alloys are half-metallic within the whole studied range. The local magnetic moments of Fe atoms are found to be antiferromagnetically aligned with those of Cr and Co atoms. This causes a decrease of the total magnetic moments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The results indicated that Co 2-x Fe x CrAl alloys are half-metallic within the whole range and that the total spin moment decreases as a function of Fe concentration. 11 We also performed calculations for the stoichiometric and non-stoichiometric Co 2 VSn alloy. 12,13 The perfect structure of this alloy was found to exhibit a half-metallic behavior with a band gap of 0.56 eV in the minority spin channel.…”
mentioning
confidence: 99%
“…The results indicated that Co 2-x Fe x CrAl alloys are half-metallic within the whole range and that the total spin moment decreases as a function of Fe concentration. 11 We also performed calculations for the stoichiometric and non-stoichiometric Co 2 VSn alloy. 12,13 The perfect structure of this alloy was found to exhibit a half-metallic behavior with a band gap of 0.56 eV in the minority spin channel.…”
mentioning
confidence: 99%
“…For example, the structural, electronic and magnetic properties of the Fe doped half-Heusler and Heusler compounds CoFe x CrAl and Co 2-x Fe x CrAl (x = 0, 0.25, 0.5, 0.75, 1.0), respectively, have been studied both experimentally 7 and theoretically. 8 In this paper, we use density-functional theory (DFT) and experiment to investigate chemical disorder in CoFeCrAl and the effect of the partial substitution of Si for Al. Chemical disorder tends to transform the spin-gapless semiconductor (SGS) into half-metallic magnets.…”
Section: Introductionmentioning
confidence: 99%